Blood metal ion release after primary total knee arthroplasty: A Prospective Study - Reiner, Tobias; Sorbi, Reza; Müller, Maike; Nees, Timo A.; Kretzer, Jan Philippe; Rickert, Markus; Moradi, Babak (Orthopaedic surgery, 2020)
Objectives - To investigate the course of in vivo blood metal ion levels in patients undergoing primary total knee arthroplasty (TKA) and to investigate potential risk factors associated with metal ion release in these patients.
Gesehen am 22.12.2020